Isotopic fingerprints of benthic nitrogen cycling in the Peruvian oxygen minimum zone. (15th January 2019) - Dale, A.W.; Bourbonnais, A.; Altabet, M.; Wallmann, K.; Sommer, S.
Abstract: Stable isotopes ( 15, 14 N, 18, 16 O) of dissolved inorganic nitrogen (N) were measured in sediment porewaters and benthic flux chambers across the Peruvian oxygen minimum zone (OMZ) from 74 to 1000 m water depth. Sediments at all locations were net consumers of bottom water NO3 − . In waters shallower than 400 m, this sink was largely attributed to dissimilatory nitrate reduction to ammonium (DNRA) by filamentous nitrate-storing bacteria ( Marithioploca and Beggiatoa ) and to denitrification by foraminifera. The apparent N isotope effect of benthic NO3 − loss ( 15 εapp ) was 7.4 ± 0.7‰ at microbial mat sites and 2.5 ± 0.9‰ at the lower fringe of the OMZ (400 m) where foraminifera were abundant. The OMZ sediments were a source of 15 N-enriched NO2 − (28.9 to 65.5‰) and NH4 + (19.4–20.5‰) to the bottom water. Model simulations generally support a previous hypothesis attributing the 15 NH4 + enrichment to a coupling between DNRA and anammox (termed DAX) using biologically-stored NO3 − from Marithioploca and NH4 + from the porewater. The model predicts that 40% of NO3 − that is actively transported into the sediment by Marithioploca is reduced to N2 by this pathway. DAX enhances N2 fluxes by a factor of 2–3 and accounts for 70% of fixed N loss to N2 . Moreover, because most of the ambient porewater NH4 + is generated by DNRA, up to two-thirds of biologically-transported NO3 − could end up being lost to N2 . This challenges the premise that Marithioploca -dominated sediments tend to conserve fixed N. By limiting the flux of 15 NH4 + back to the ocean, DAX also tends to decrease benthic N fractionation. Tracking the fate of NH4 + once it leaves the sediment is critical for understanding how the benthos contributes to N isotope signals in the water column.